Pedagogic Meaning-Making in Spherical Video-Based Virtual Reality – a Case Study from the EFL Classroom - Volker Eisenlauer; Diana Sosa (Designs for Learning)
This article explores relevant conceptual frameworks and design principles for the planning and implementation of a virtual reality (VR) learning environment in English as a foreign language (EFL) contexts. The primary focus is on what knowledge teachers need to acquire when designing and implementing a spherical video-based training world that allows English learners to experience the different phases of an oral examination in English. Therefore, the paper introduces the educational potential and affordances of spherical videos and describes structural and contextual aspects of oral examinations in English. Employing a prototype learning environment, we expand on major learning theories in spherical video-based learning and suggest best practices for the design and implementation of immersive learning experiences in EFL contexts.